KAJIAN RELEVANSI KURIKULUM TERHADAP KOMPETENSI KERJA ALUMNI JURUSAN PENDIDIKAN GURU MADRASAH IBTIDAIYAH IAIN ANTASARI BANJARMASIN - Husaini, Rusdiana Husani; Kurdi, Musyarrafah Sulaiman (Journal of Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2015)
This study aimed to identify the profile and relevance of curriculum or courses in Primary Teacher Education and Training Department of State Institute for Islamic Studies Antasari Banjramasin to occupation competence. The research method is a survey approach and the type is descriptive exploratory study. The subject of research are graduates in Primary Teacher Education and Training Department in 2011-2013, academic users and non-academic users. The results showed: 1. Profile of a graduate in primary that has become part of society show that: (a) 75.76% of graduates have been very ready to enter the job market; (B) 60.61% is very easy to get a job; (C) 75.76% has the ability to create the job market (d) 78.79% worked as a temporary teacher in Islamic Primary School; (E) Competence with very high criteria is 48.48% (pedagogical competence), 54.54% (personal competence), 54.55% (professional competence), and 84.85% (social competence). 2. Courses in the 2007 curriculum had some subjects that are less relevant, they are need to be revised. 3. the necessary competence is pedagogical, professional, personal, and social competence; job readiness; the seriousness of the work; communications; cooperation; independence; creativity; the use of foreign languages; use of information technology; the attitude of the leadership; willingness fast forward; analysis; writing reports; acceptance of new things; self-development; ductility; science-based expertise and integrity. 4. In the opinion of users academics and non-academics competence of graduates has been very satisfactory, fairly competent and have sufficient capability.